Substance use, situational characteristics and sexual outcomes in men who have sex with men - Melendez-Torres, GJ (2014)
This thesis presents an empirical investigation into substance use, situational characteristics and sexual outcomes in men who have sex with men (MSM) motivated by the high rates of substance use in MSM; the association between substance use and sexual risk behaviours in MSM; the lack of specific theory addressing relationships between substance use, sexual interactions and social interactions between MSM; and the need for clearer understandings of encounter-level associations with sexual risk. Qualitative metasynthesis. This thesis begins with laying the methodological groundwork for a qualitative metasynthesis that theorises the relationship between substance use and social spaces in MSM, with a particular focus on sexual outcomes. The qualitative metasynthesis derives the key organising perspective of ‘littoral spaces’ in which substance use is associated with a pre-planned, though temporary, escape from the boundaries of everyday life to engage in maximal sensory exploration, including through sexual contact. Systematic review of multiple-event analyses. The thesis then turns to a systematic review of previous quantitative multiple-event analyses examining associations between situational characteristics and sexual outcomes, which establishes the need for additional multiple-event analyses addressing specific substance use, location of sex, partner serodiscordance and partner type. Multiple-event analyses. Finally, informed by the qualitative metasynthesis and the systematic review of event-level analyses, this thesis presents multiple-event analyses addressing unprotected anal intercourse (UAI), pleasure and control as sexual outcomes in MSM in England. These analyses found that substance use was associated with greater odds of UAI and pleasure, but not with control, and that non-private locations of sex were associated with decreased odds of UAI and pleasure, but not control. Furthermore, there was sparse evidence of interactions between respondent and partner substance use and between respondent substance use and location of sex in associations with sexual outcomes. These analyses contribute to understandings of associations between substance use, situational characteristics and sexual risk behaviour by presenting the first known analyses on MSM in England and by examining sexual outcomes besides UAI.